Perceived mate competition risk influences the female mate choice and increases the reproductive effort in the annual killifish Millerichthys robustus. Issue 2 (4th March 2022) - Domínguez-Castanedo, Omar
Abstract : Female life-history strategies can be sensitive to social context, responding adaptively to current or future mate limitations by reproductive competition conditions. Competitive environments provide the conditions for adjusting reproductive decisions in order to compensate for the negative impacts of competition between individuals, thus maintaining reproductive fitness. This research aimed to test the effect of perceived competition risks for mate choice and their consequences in the reproductive effort of females of the annual killifish Millerichthys robustus induced throughout an audience effect. First, I evaluated the female mate choice using a classic dichotomous preference study based on male size, showing that the females do not show a significant preference for males of any size in a scenario without perceived competition; however, females turn selective under competition risk, choosing the large males. I then evaluated the reproductive effort of females through embryo production without an audience for 10 days, and next with an audience of females for two periods of 10 days. Results showed that females produced significantly more embryos when they perceived a risk of competition. Also, females turn selective under risk of competition, probably due to an increased parental investment expressed by the reduction of the female-male encounters and breeding rate, the increased reproductive effort and the time spent searching a mate. Females that mate with larger males may gain access to more benefits derived from his social status, as best territories and high-quality sites for the spawn, thus increasing the probabilities of survival for the females and their offspring. I propose that, as a life-history strategy to preserve individual fitness, the direction of the sexual selection is modified by the perceived competition risk, and that competition is not necessarily related with the high-cost investments; in fact, it may also have, beneficial effects for the individual female reproductive success.